Profile of the Use of Microorganisms within Environmental Management : Systematic Review 2012-2017 (2020)
ABSTRACT : The use of microorganisms as part of environmental management action, aimed at dealing with environmental issues, results in an interesting and more environmentally friendly alternative to the conventional physicochemical decontamination methods. In this sense, a profile of the use of microorganisms in environmental management would prove helpful for people and organizations to make their processes more sustainable. However, the publications that describe the use of microorganisms within environmental management tend to show their author’s point of view, rather than the results of a systematic study in this field of knowledge. Consequently, descriptions of microorganisms, environmental issues and economic sectors involved do not necessarily reflect how developed research in microbiology and environmental management is. Therefore, the aim of this study was to describe the use given to microorganisms within environmental management, providing a profile related to the environmental issues tackled, natural resources affected, and economic sectors involved. A systematic review of scientific literature published between 2012 and 2017 led us to the description of three types of use given to microorganisms, six types of natural resources protected through such uses, ten types of environmental issues, and eight economic sectors in which the uses mentioned are applicable.